"Does global sourcing pay-off? A competitive dynamics perspective". Issue 4 (December 2016) - Vos, Frederik G.S.; Scheffler, Paul; Schiele, Holger; Horn, Philipp
Abstract: The supposed benefits of global sourcing in supply chain management remain subject to debate. Here this study investigates the potential benefits of global sourcing using a large dataset obtained from a leading European automotive original equipment manufacturer, spanning a period of five years. Contrary to expectations, this study found no evidence that low-wage country sourcing leads to cost reductions relative to sourcing from suppliers based in industrialized countries. However, the data does show that global sourcing induces increased competition within the industrialized country supply base when low-wage country suppliers participate in negotiations. Additionally, a new method for assessing competitive dynamics in supply markets is introduced. Highlights: It is assessed whether low-wage country (LWC) sourcing increases competitive dynamics. The sample consists of 15, 891 sourcing projects from 2008-2012 of an automotive OEM. A new measure for assessing competitive dynamics in supply markets is introduced. Results show that LWC sourcing does not automatically lead to cost reductions. Still, LWC suppliers increase competitive dynamics during price negotiations by 2.34%